2004
DOI: 10.3748/wjg.v10.i24.3590
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti-apoptosis and gut epithelium protection function of acidic fibroblast growth factor after cancelling of its mitogenic activity

Abstract: These findings emphasize the importance of non-mitogenic effects of aFGF, and have implications for its therapeutic use in preventing apoptosis and other injuries in tissues and internal organs triggered by ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…Several reports have described antiapoptotic actions of FGF-1 in cardiac and vascular smooth muscle (4,8,9), as well as in other cell types (12,51), in part through receptorstimulated activation of the MAP kinases ERK-1 and -2 (4). In agreement with the hypothesis that local production of FGF-1 could account for some of the effects of p300 on muscle cell survival, we found that conditioned culture medium from cells expressing p300 wt but not p300 wt ϩDox increased myoblast viability and could activate ERK-1 and -2.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described antiapoptotic actions of FGF-1 in cardiac and vascular smooth muscle (4,8,9), as well as in other cell types (12,51), in part through receptorstimulated activation of the MAP kinases ERK-1 and -2 (4). In agreement with the hypothesis that local production of FGF-1 could account for some of the effects of p300 on muscle cell survival, we found that conditioned culture medium from cells expressing p300 wt but not p300 wt ϩDox increased myoblast viability and could activate ERK-1 and -2.…”
Section: Discussionmentioning
confidence: 99%
“…The first series of media contained different concentrations of glucose (0, 1, 2 and 5 g/l) and the second series contained mannose (10,12,15,20 and 30 g/l) along with 5 g/l glucose.…”
Section: Dose Response Curve For Mannosementioning
confidence: 99%
“…It takes part in multiple biological processes, including embryonic development, cell growth, morphogenesis, angiogenesis and tissue repair. Acidic FGF has been examined as therapeutic protein in animal and clinical trials for skin wound and burn healing (44), wound healing of diabetic patients (62), angiogenesis (22,49), neurotrophic activity (30,64), strong anti-apoptotic function (14,68), gut epithelium protection (20), spinal cord injury repair (65). New lymph vessels growth as well as recovery of injured ischemic blood vessels is increased when using therapy with aFGF (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of the N-terminal of aFGF gene and elimination of N terminal residues 1-27 plus methionine substitution of leucine at the site of 27 yields a human acidic fibroblast growth factor mutant (haFGF27-154), that is, modified aFGF (MaFGF) [8,9]. It has been shows that when the N-side 1 to 27 amino-acid residue of aFGF is removed, its mitogenic activity is lost or obviously decrease, but its non-mitogenic effect still exists [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%